Quest for malaria management using natural remedies - Ain, Qura Tul; Saleem, Nida; Munawar, Nayla; Nawaz, Rukhsana; Naseer, Faiza; Ahmed, Sagheer (Frontiers in Pharmacology, 2024)
Malaria, transmitted through the bite of a Plasmodium-infected Anopheles mosquito, remains a significant global health concern. This review examines the complex life cycle of Plasmodium, emphasizing the role of humans and mosquitoes in its transmission and proliferation. Malarial parasites are transmitted as sporozoites to the human body by biting an infected female Anopheles mosquito. These sporozoites then invade liver cells, multiply, and release merozoites, which infect red blood cells, perpetuating the cycle. As this cycle continues, the affected person starts experiencing the clinical symptoms of the disease. The current treatments for malaria, including chloroquine, artemisinin-based combination therapy, and quinine, are discussed alongside the challenges of drug resistance and misdiagnosis. Although efforts have been made to develop a malarial vaccine, they have so far been unsuccessful. Additionally, the review explores the potential of medicinal plants as remedies for malaria, highlighting the efficacy of compounds derived from Artemisia annua, Cinchona species, and Helianthus annuus L., as well as exploration of plants and phytocompounds like cryptolepine, and isoliquiritigenin against drug-resistant Plasmodium species. Moreover, studies from Pakistan further highlight the diverse vegetal resources utilized in malaria treatment, emphasizing the need for further research into natural remedies. Despite the advantages of herbal medicines, including cost-effectiveness, and fewer side effects; their limitations must be taken into account, including variations in potency and potential drug interactions. The review concludes by advocating for a balanced approach to malaria treatment and prevention, emphasizing the importance of early detection, accurate diagnosis, and integrated efforts to combat the disease in the endemic regions.